South Africa’s Failure to Arrest President al-Bashir : An Analysis of the Supreme Court of Appeal’s Decision and its Implications - Pavlopoulos, Nikolaos (Comparative and International Law Journal of Southern Africa, 2020)
The ICC and many of its state parties disagree over whether President al-Bashir is entitled to respect for his immunities from those states. On the one hand, the ICC has requested al-Bashir's surrender, while, on the other, its state parties have refused to cooperate. The ICC's Pre-Trial Chamber has provided various justifications for its stance - that state parties are obliged to surrender al-Bashir - the most recent relating to the effect of the SC referral which gave the ICC jurisdiction on al-Bashir's immunities. The African Union has, however, consistently held that its member states, including those that are party to the Rome Statute, remain obliged to respect its immunities. It is argued that South Africa's Supreme Court of Appeal avoided engaging with the core issues in this debate, namely the scope of the obligation to comply with ICC requests for arrest and surrender as well as the arguments adopted by the PTC in finding that al-Bashir's immunities need not be respected. The SCA's approach is unwarranted in light of domestic principles of interpretation and also unjustifiably undermines the customary international law on immunities ratione personae. Ultimately, the court's reluctant engagement with the international legal issues can only serve to undermine the coherence of the international legal system and perpetuate the harm the ICC is doing to itself in persisting that its state parties are obliged to arrest President al-Bashir.